2007
DOI: 10.1038/bdj.2007.725
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of dental extractions, suturing and INR on postoperative bleeding of patients maintained on oral anticoagulant therapy

Abstract: Dental extractions may be safely performed for patients on anticoagulation therapy provided the INR level is kept <3.0 and effective measures of local haemostasis are administered. The decision to suture should be made on case-by-case basis, as the trauma associated with soft tissue handling might outweigh its advantages in certain situations like simple extractions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
63
0
18

Year Published

2010
2010
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 87 publications
(85 citation statements)
references
References 46 publications
4
63
0
18
Order By: Relevance
“…On the other hand, several observational studies demonstrated the safety in performing invasive procedures for patients with thrombocytopenia whom did not receive any prophylactic PLT transfusions. These findings support the notion that in patients with INR < 3.0, it is relatively safe to perform tooth extraction without a significant increase in the risk of bleeding [2].…”
supporting
confidence: 87%
“…On the other hand, several observational studies demonstrated the safety in performing invasive procedures for patients with thrombocytopenia whom did not receive any prophylactic PLT transfusions. These findings support the notion that in patients with INR < 3.0, it is relatively safe to perform tooth extraction without a significant increase in the risk of bleeding [2].…”
supporting
confidence: 87%
“…Malgré la simplification des procédures, une prudence s'impose chez les patients très âgés qui cumulent bien souvent de nombreux facteurs associés à une augmentation du risque de saignement. [20,46,249,254,263] Non contrôlé par des mesures hémostases locales 0 % à 26 % [28,33,41,46,51,55,82,99,114,115,126,209,249,254,255,263,283] Hémorragie sévère, 0 % à 2,77% [28,33,41,46,51,55,82,99,114,115,126,209,249,254,255,263,283] Poursuite • Pour limiter le risque de saignement, il est nécessaire d'ajuster le TCA préop en dessous de 57 sec.…”
Section: Resultsunclassified
“…Dans une grande série de cas prospectif (n = 500), Cocero et coll., 2014 [63] Au total, 26 études observationnelles prospectives randomisées [17,19,20,28,33,41,42,45,46,51,55,57,58,82,99,114,126,181,209,223,249,254,255,263,269,290], présen-tées dans l'annexe 7, ont évalué l'intérêt de l'utiliser des hémos-tatiques locaux spécifiquement en chirugie dento-alvéolaire.…”
Section: Quel Test Biologique Doit-on Utiliser Pour éValuer Le Risqueunclassified
See 1 more Smart Citation
“…En chirurgie buccale, dans la plupart des publications, aucune relation statistique n'a été retrouvée entre le taux de l'INR préopératoire et le risque hémorragique [11][12][13][14][15]. En outre, aucune étude n'a montré de différence dans l'incidence du saignement entre la pratique des extractions dentaires en poursuivant les AVK aux doses thérapeutiques avec un INR compris 2,00 et 4,50 en réalisant une hémostase locale, versus l'arrêt des anticoagulants oraux et la réalisation des actes avec un INR inférieur à 2,00 ou 2,50 [16][17][18][19][20][21][22].…”
Section: Discussionunclassified